PEMANFAATAN BIOCHAR BERBAHAN DASAR AMPAS TEBU (Saccharum Officinarum Linn) SEBAGAI BAHAN PEMBENAH TANAH PADA LAHAN BEKAS TAMBANG BATUBARA - Elma Nazella (Fakultas Teknologi Mineral, Universitas Pembangunan Nasional (UPN), 2022)
Mining activities in South Kalimantan are carried out openly which have an impact on changes in soil structure due to excavation of top soil to reach deeper layers of mining material. The soil in the mining area is infertile with a high acidity level with very low nutrients, water retention, unstructured, and the content of elements is toxic. Therefore, it is necessary to carry out treatment through remediation of mining land to restore the carrying capacity of the soil. One alternative that can be used is biochar made from bagasse. This study aims to determine the characteristics of bagasse biochar and see the effect of using bagasse biochar with variations in dosage and contact time on the soil improvement process in stabilizing pH and eliminating soil Fe levels. The soil remediation process was carried out on a laboratory scale with various doses of biochar (0 g, 7.5 g, 15 g and 30 g) and contact time (15 days, 30 days, and 45 days). The results showed that bagasse biochar has characteristics that meet the requirements as a soil enhancer based on pH, C/N ratio, organic C, total N, CEC, total P, total K, ash content and water content. The results of remediation carried out for 45 days showed that bagasse biochar was able to neutralize the initial pH from 4.9 to 6.9 and was able to reduce Fe levels by 8158.1 mg/kg.Keyworld: Biochar, Sugarcane Bagasse Mining Land, Heavy Metal (Fe), pH